Exploring underwater archaeology findings with a diving simulator in virtual reality - Plecher, David A.; Keil, Leonard; Kost, Guy; Fiederling, Max; Eichhorn, Christian; Klinker, Gudrun (Frontiers in Virtual Reality, 2022)
With Virtual Reality (VR) technology maturing and spreading widely in recent years, it is becoming an increasingly useful tool for entertainment and education alike. Its potential to simulate hard to reach environments and emulate unique experiences believably could be of great interest for the scientific study of Underwater Cultural Heritage (UCH), in particular for the simulation of real-world dives. VR enriched with techniques from immersive Serious Games could provide an authentic way to enjoy UCH and the sport of diving from the comfort of the user’s home or as a museum exhibit. In this paper we are focusing on the exploration on the wreck of a Roman merchant ship from the 5th century AD, which was found near Veliki Piruzi (Croatia). The images taken by the underwater archaeologists enable a 3D reconstruction of the excavation site.